Beyond Authoritarian Personality: The Culture-Inclusive Theory of Chinese Authoritarian Orientation - Chien, Chin-Lung (Frontiers in Psychology, 2016)
In a dyad interaction, respecting and obeying those with high status (authority) is highly valued in Chinese societies. Regarding explicit behaviors, Chinese people usually show respect to and obey authority, which we call authoritarian orientation. Previous literature has indicated that Chinese people have a high degree of authoritarian personality, which was considered a national character. However, under Confucian relationalism (Hwang, 2012a), authoritarian orientation is basically an ethical issue, and thus should not be reduced to the contention of authoritarian personality. Based on Yang’s (1993) indigenous conceptualization, Chien (2013) took an emic bottom-up approach to construct an indigenous model of Chinese authoritarian orientation; it represents a “culture-inclusive theory.” However, Chien’s model lacks the role of agency or intentionality. To resolve this issue and to achieve the epistemological goal of indigenous psychology (that is, “one mind, many mentalities”), this paper took the “cultural system approach” (Hwang, 2015b) to construct a culture-inclusive theory of authoritarian orientation in order to represent the universal mind of human beings as well as the mentalities of people in a particular culture. Two theories that reflect the universal mind, the “Face and Favor model” (Hwang, 1987) and the “Mandala Model of Self” (Hwang, 2011a, 2011c), were used as analytical frameworks for interpreting Chien’s original model. The process of constructing the culture-inclusive theory of authoritarian orientation may represent a paradigm for the construction of indigenous culture-inclusive theories while inspiring further development. Some future research directions are proposed herein.